Mediating lack of social interaction and financial stress in domestic violence during Covid-19: post covid-19 policy scenario in pakistan - Suleman, Danish; Iqbal, Faiza; Bhatti, Laiba Iqbal (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
The COVID-19 pandemic that has shaken the global economy, production and trade has also impacted social and domestic life. In this study, the impact of COVID-19 has been investigated on lack of social interaction, financial stress, and how it affects domestic violence in a developing country like Pakistan. The modified scale has been validated using confirmatory factor analysis. Purposive sampling and snowball sampling techniques were used to collect data from 200 respondents in Punjab, Pakistan, for data analysis through SPSS and SmartPLS. The results showed that COVID-19 has a significant influence on lack of social interaction and financial stress. Lack of social interaction and financial stress also increased domestic violence during covid-19. This study appears to be the leading research determining the impact of COVID-19 on lack of social interaction, financial stress, and domestic violence, especially in a developing country like Pakistan.